Enhancing Learners’ Engagement and Performance in Learning through E-Resources and Services: National Open University of Nigeria Students as Beneficiaries - Patricia Ngozi Ofodu; Loveth Ogoegbunam Ekwueme (West African Journal of Open and Flexible Learning)
Enhancement of performance on learning among learners has been on the increase due to digital information and technologies provided by libraries, because of its backbone in academic pursuit. This study investigates enhancing learners’ engagement and performance in learning through e-resources and services. The study was guided by four research questions with two hypotheses, which examined the availability of e-resources, the frequency of usage, the influence of usage and the factor undermining the usage of electronic resources. The findings from the study revealed that there are some e-resources available for the users’; there are users that are making use of the electronic resources occasionally and daily, while some don’t use e-resources at all. The study also revealed that the use of electronic resources influenced the users’ class tests, assignments, seminar presentations and more, while there was also evidence of non-assistance from the use of e-resources in some students’ learning pursuits. The study equally revealed some of the factors undermining the use of e-resources including inadequate power supply, poor internet connectivity, lack of technology competence and limited access to computer terminals, etc.